Revising Anthropocentrism of Technics in the Light of the 21st Century New Anthropological Models - Melnyk, V. P; Lushch-Purii, U. I (Anthropological Measurements of Philosophical Research, 2022)
Purpose. To substantiate the definition of technics as the attributive characteristics of a human being and the necessity of its orientation towards human flourishing in the context of new anthropological models of the 21st century. Theoretical basis. Correlation between technics, technology and the human essence is examined. The role of technics is traced at different historical stages of human development. Negative and positive effects of digital technology development upon a contemporary human being is analysed in the light of new anthropological models: homo technologicus, homo digitalis and homo eudaimonicus. The content of a new worldview-value paradigm of defining goals of technology is outlined. Originality. Transformation of the role of technics correlates with value and worldview shifts in person’s understanding of his/her purpose in both natural and social worlds. Nowadays, philosophical analysis of anthropological dimension of technics and technology opens a horizon for seeking effective solutions in the face of the contemporary challenges and anti-utopian threats by means of focusing on the fact that, indeed, technological development is subordinate to the humanist goal that is flourishing, wellbeing and comprehensive development of a human being. Conclusions. The essence of technology reveals not through its functional but anthropogenic definitions in a sense of a source of institutionalization and in a sense of a source of realization of a human way of self-identification and self-objectification of human subjectivity. Technics/technology is the attributive characteristics of human essence and being: a human being is as much human as much he/she is a creator of technics. The purpose of technics is not to master the nature and to transform the world; technics is, above all, a tool of human self-improvement and self-creation through broadening the horizon of human capacities. The analysis of new modern anthropological models shows that it is the orientation of technology/technology towards human flourishing that is, on the one hand, a response to the existential demands of modern man, and on the other hand, a way of preventing future threats related to technological development.